Principles, role and value of planning - Thibert, H. (The Professional Skater PS Magazine, 2014)
The information is excerpted from the Coaches Guide to Figure Skating Sport Science and Medicine 3rd Ed, authored by Charlcnc Boudreau. This article incorporates the Physical Conditioning Domain #3 as defined by the National Association tor Sport and Physical Education